Scent and cues in the forage for Information : the roles of task and topical knowledge in the evaluation of information patch - Lee, Helena Seow Hong (2018)
Information seeking is an effortful task that involves user effort in filtering through hyperlinks and visual elements such as image and text. However, there is a lack of studies on the topic. This dissertation examines how hyperlink and visual elements and task specificity interacts to affect user effort during information seeking. This research employs a mixed-method approach using an eye-tracking tool to analyse link-clicks and eye-fixations of hyperlinks and visual elements. In addition, post-experiment interviews and questionnaire surveys were administered to understand the individual’s insights and meanings of their information behaviour. It is also to ensure a level of consistency accounting for the quantitative analysis. The results showed that users incurred varied effort in engaging the hyperlinks. Hyperlinks play an important role in prompting users’ action where they adopt the filtering techniques during information seeking. Furthermore, the findings revealed that task specificity interacts with effort and evaluation. This research has shed light on the association of hyperlinks and visual element that reduce information seeking effort through aiding navigation, while the hyperlink aesthetic affects information evaluation. Task specificity interacts with hyperlink such that when task specificity is high, the effect of hyperlink aesthetics on effort is low. The research contributes to guiding information provider and web designer to facilitate users’ and consumers’ information seeking in terms of the hyperlink structure and positioning of hyperlinks while accounting for task specificity.